PERAN INKLUSI KEUANGAN TERHADAP PEMBANGUNAN EKONOMI: STUDI KASUS KAWASAN ASEAN-2 - Liasulistia Ningsih; Indra Ismayudi Tanjung; Hartini; Aglis Andhita Hatmawan; Noval Suhendra (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Financial inclusion refers to a condition where every member of society has access to various formal financial services. Easy access to financial products and services is expected to provide great opportunities for both companies and households to increase income and independence which has a positive impact on the development economy. Each country has different financial inclusion policies according to the economy and socio-cultural characteristics, but has the same goal, namely to develop the economy and reduce poverty. Given the importance of cooperation that has been carried out by ASEAN member countries in increasing financial inclusion through Digital Financial Services (DFS), this study will analyze the role of financial inclusion in economic development in the ASEAN region. Therefore, various variables are studied in this study, including the number of bank branches, the number of ATMs, and domestic credit which are indicators of financial inclusion and the economic development index as dependent variables. The analysis in this study uses quantitative analysis with the panel regression analysis method. The data used in this study uses the period from 2009-2020. The countries used in the analysis of this study come from 8 member countries that are members of ASEAN. The results of the analysis found that financial inclusion has an impact on economic development, this is reflected in the variables of the number of ATMs, the number of bank branches and domestic credit which have a significant impact on economic development